Effect of feeding oak leaves on nutrient utilization and growth performance of goats in Kumaon hills of temperate sub Himalayas - MINZ, PIYUSHA S D; SAHOO, B; GARG, A K; SHANKAR, M; SHARMA, A K (The Indian Journal of Animal Sciences, 2013)
A 120 days of growth study was conducted on goats to assess the effect of tanniniferous oak leaves (Quercus semecarpifolia) on nutrient utilization and growth performance. Growing kids (18) of 7–9 month-old (13.13±0.99 kg) were randomly divided into homogenous groups T1, T2 and T3 of 6 in each. All the animals were fed same concentrate mixture but, the roughage source was different and the concentrate: roughage source was maintained at about 40: 60 ratio. Native grass hay (Heteropogon contortus) was fed in T1 and T3 which was replaced by oak tree leaves in T2. Tannic acid was supplemented in T3, at par with the hydrolysable tannin content in oak leaves fed to T2. A metabolic trial of 6 days duration was conducted after 90 days of growth trial. DM intake through roughage (oak leaves) in T2 was higher than T1 and T3. The total DM intake (g d-1 kg-1W°.75) was also higher in T2 than T1 and T3. The nutrient digestibilities were similar except ether extract digestibility which was higher in T2 than T1 and T3. N balance (g d-1) was similar in all 3 groups. However, N retention as percent of absorbed nitrogen was higher in T2 than T3, but at par with T1. Average daily gain (g d-1) was higher in T2 (60.36) than T1 (38.12) and T3 (26.46) which were at par. Feed gain ratio (DMI/unit body weight gain) was comparatively better in T2 (12.93) than T3 (23.24) but at par with T1 (17.29). It was concluded that feeding of oak leaves (CT, 0.85% and HT, 4.4% in diet) improved nutrient utilization, growth performance and feed efficiency in kids compared to animals fed local grass hay with or without supplementation of tannic acid.